The Influence of Social Phenomenon on the Contemporary Ecological Crisis in the Light of the Encyclical Laudato Si’ - Sadowski, Ryszard F. (Studia Ecologiae et Bioethicae, 2017)
In the encyclical Laudato Si’. On Care for our Common Home, Pope Francis sums up the rich legacy of his predecessors contained in the statements on the ecological question. The Pope’s standpoint actively involves the community of the Catholic Church into the mainstream of the contemporary environmental debate. It seems, that the Pope designates those social phenomena that have a particularly significant impact on the modern ecological crisis. The most important among them is the intimate relationship between the poor and the fragility of the planet, the throwaway culture, the new ways of understanding progress, and the proposal of a new lifestyle.